Non-Genomic Actions of the Androgen Receptor in Prostate Cancer - Leung, Jacky K.; Sadar, Marianne D. (Frontiers in Endocrinology, 2017)
Androgen receptor (AR) is a validated drug target for prostate cancer based upon its role in proliferation, survival, and metastases of prostate cancer cells. Unfortunately, despite recent improvements to androgen-deprivation therapy and the advent of better antiandrogens with a superior affinity for the AR ligand-binding domain, most patients with recurrent disease will eventually develop lethal metastatic castration-resistant prostate cancer. Expression of constitutively active AR splice variants that lack the ligand-binding domain contribute towards therapeutic resistance by bypassing androgen blockade and antiandrogens. In the canonical pathway, binding of androgen to AR ligand-binding domain triggers the release of AR from molecular chaperones which enable conformational changes and protein-protein interactions to facilitate its nuclear translocation where it regulates the expression of target genes. However, preceding AR function in the nucleus, initial binding of androgen to AR ligand-binding domain in the cytoplasm may already initiate signal transduction pathways to modulate cellular proliferation and migration. In this article, we review the significance of signal transduction pathways activated by rapid, non-genomic signaling of the AR during the progression to metastatic castration-resistant prostate cancer and put into perspective the implications for current and novel therapies that target different domains of AR.